Extended averaged equation method and application on analyzing some nonlinear deterministic vibrations - Anh, Nguyen Dong; Hai, Ninh Quang; Schiehlen, Werner (Vietnam Journal of Mechanics, 2009)
The paper presents an extended averaged equation approach to the investigation of nonlinear vibration problems. The proposed method is applied to some free/self excited oscillator, nonlinear free and forced oscillations of a suspension system with two-degree-of-freedom. The results in analyzing the vibration systems with different nonlinearity show the efficiency and advantages of the method